Mengadaptasi Kepemimpinan Perguruan Tinggi dengan 18 Nilai Karakter Bangsa (Studi Literatur) - Danang Nugroho; Tasya Alfia Salsa Nabila; Salma Agustina; Sindi Setiawati; Sawitri Rahmawati; Sovi Alawiyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Effective leadership plays a pivotal role in achieving quality higher education. This study delves into how leadership management in higher education institutions can be aligned with the 18 national character values of Indonesia. Employing a Systematic Literature Reviews (SLR) methodology, the study analyzes literature pertaining to leadership, education quality, and national character values. The findings underscore the paramount importance of effective and professional leadership in enhancing the quality of higher education. Effective leaders must possess the competencies and qualities to manage, guide, cultivate, and steer all components of the higher education institution towards achieving educational goals. The new leadership management model proposed in this study integrates the 18 national character values of Indonesia into leadership styles. These values encompass religiousity, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, nationalism, patriotism, appreciation for achievement, friendliness/communicativeness, peacefulness, love of reading, environmental awareness, social responsibility, and accountability. Implementing national character values into leadership is expected to encourage followers to work voluntarily and enthusiastically towards achieving shared goals. Ultimately, this will lead to the enhancement of higher education quality in Indonesia.